Импульсный режим горения несамостоятельного дугового разряда с накаленным и полым катодами; Известия вузов. Физика; Т. 58, № 9-2 - Денисов В. В. Владимир Викторович; Ковальский С. С. Сергей Сергеевич; Яковлев В. В. Владислав Викторович; Коваль Н. Н. Николай Николаевич (2015, 2015)
Заглавие с экрана